Gene isolation of callose synthase in a tropical timber tree neolamarckia cadamba - Tan, Shin Heng (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Neolamarckia cadamba, commonly known as Kelampayan is tropical timber distributed naturally in Southeast Asia. Kelampayan possesses various great commercial values and it is a good material used in the paper and pulp industry. Callose synthase is an important enzyme to synthesize callose for the defence system besides growth and development of the plant. The main objective of this study was to isolate and characterize the partial genomic sequence of callose synthase gene from Kelampayan. Specific primer pair was designed and synthesized. Optimization strategies of Polymerase Chain Reaction (PCR) were performed to determine the optimal condition for the gene amplification. The callose synthase gene was amplified with the specific primer and subsequently examine on 1.5% agarose gel. The purified DNA with approximately 800 bp and primers were sent for sequencing and data obtained was analyzed. The data was subjected to BLASTn analysis to search for sequence homology against nonredundant nucleotide database· in NCBI. The result showed that the extracted amplicons was not callose synthase gene.